A longitudinal study of perinatal depression and the risk role of cognitive fusion and perceived stress on postpartum depression. Issue 5 (2nd May 2022) - Liu, Wenting; Wu, Xiaxin; Gao, Yuanmin; Xiao, Chaoqun; Xiao, Julan; Fang, Fan; Chen, Yu
Abstract: Aims and Objectives: To explore fluctuations in perinatal depression based on physiological, psychological and interpersonal dimensions to analyse risk factors across three time points: in the third trimester and at weeks 1 and 6 postpartum. Background: Pregnant women experience depression at multiple time points and require screening. Studies have shown protective and negative factors related to postpartum depression. Cognitive fusion refers to an individual's emotions and behaviours that are regulated and influenced by that individual's own cognitive overregulation, especially when facing stress. This is an important psychological factor related to depression, but little is known about it in pregnant women. Design: A longitudinal study was conducted from June 2019–July 2020, and the findings are reported following the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines. Methods: Pregnant women ( n  = 207) were recruited, and a questionnaire survey was performed at 32–34 weeks of pregnancy and at weeks 1 and 6 postpartum. Repeated‐measures analysis of variance was performed to analyse the changes in depression over time. Regression analysis and linear mixed modelling were used to identify risk factors. Pearson's correlation analysis was performed to analyse the relationships between variables. Results: Of the pregnant women, 36.70% experienced antenatal depression and prolonged depression with the onset of postpartum depression (12.21%). Some depressive moods disappeared spontaneously after delivery (47.37%). Perceived stress was the highest risk predictor of postpartum depression ( β  = 0.332), followed by cognitive fusion ( β  = 0.178), which remained stable over time and might have been positively related to having a vulnerable personality (0.2 <  r  < 0.4). Social support plays a positive role in lowering postpartum depression ( β  = −0.027). Conclusions: Changes in depression were influenced by multiple factors with stability and predictability across time. Psychological dimensions, such as perceived stress and cognitive fusion, are risk factors for developing postpartum depression and antenatal depression. Relevance to clinical practice: Pregnant women can be divided into depressive cohorts according to screening at different time points to provide targeted interventions.